2020
DOI: 10.1186/s12889-020-09483-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension care cascade in Chile: a serial cross-sectional study of national health surveys 2003-2010-2017

Abstract: Background Trend data on hypertension prevalence and attainment indicators at each step of the care cascade (awareness, treatment, control) are required in Chile. This study aims to quantify trends (2003–2017) in prevalence and in the proportion of individuals with hypertension attaining each step of the care cascade among adults aged 17 years or older, and to assess the impact of lowering the blood pressure (BP) thresholds used to define elevated BP on these indicators. Methods We used data from 2003, 2010,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Nevertheless, we found a decrease in the prevalence of hypertension between the PREFREC (2010) and ENSPA (2019) study, as opposed to other countries in the region, such as Peru, that reported an increasing prevalence of hypertension attributed to recent economic growth [ 10 ], whereas the prevalence in Brazil [ 37 ], Canada [ 7 ], and the United States [ 9 ] has remained unchanged. In agreement with our study, recent studies have reported a decrease in the prevalence of hypertension despite an increase in obesity [ 4 , 11 ]. Our results suggest that other risk factors associated with hypertension such as salt intake, smoking, and exposure to dietary fatty acids have improved [ 4 , 11 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, we found a decrease in the prevalence of hypertension between the PREFREC (2010) and ENSPA (2019) study, as opposed to other countries in the region, such as Peru, that reported an increasing prevalence of hypertension attributed to recent economic growth [ 10 ], whereas the prevalence in Brazil [ 37 ], Canada [ 7 ], and the United States [ 9 ] has remained unchanged. In agreement with our study, recent studies have reported a decrease in the prevalence of hypertension despite an increase in obesity [ 4 , 11 ]. Our results suggest that other risk factors associated with hypertension such as salt intake, smoking, and exposure to dietary fatty acids have improved [ 4 , 11 ].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our study, recent studies have reported a decrease in the prevalence of hypertension despite an increase in obesity [ 4 , 11 ]. Our results suggest that other risk factors associated with hypertension such as salt intake, smoking, and exposure to dietary fatty acids have improved [ 4 , 11 ]. For example, in the case of smoking, in 2005, Panama adopted the WHO Framework Convention on Tobacco Control.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A strength of using this strategy to obtain treatment and control rates is that centers are required to monitor this rate as obtained here. Second, it might be possible that the estimated group of people with hypertension is overestimated considering it was calculated using the prevalence reported on the last National Health Survey (2017), which shows a slight but significant decrease in the prevalence compared to the one in 2003 ( 10 ). This could underestimate the treatment and control rates calculated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is a push to improve quality of care in primary care in LMICs, especially with growing rates of DM, HTN and chronic diseases ( 27 29 ). While quality has been measured using the cascade of care of care ( 30 33 ) and achievement of guideline-based management and counseling strategies ( 34 , 35 ), fewer studies in LMICs include the role of longitudinal primary care doctors, empanelment, and the doctor-patient relationship in quality-of-care assessments ( 36 ). Given that research has shown that continuity of care improves medication adherence and patient healthy lifestyle behaviors ( 37 39 ), more research is needed on the state of continuity of care in LMICs and the doctor-patient relationship.…”
Section: Discussionmentioning
confidence: 99%